Study on concrete pumpability combining different laboratory tools and linkage to rheology. (30th July 2017) - Secrieru, Egor; Fataei, Shirin; Schröfl, Christof; Mechtcherine, Viktor
Highlights: Rheological analyses of fresh concrete and lubrication layer material are performed. Influence of roughness of the pipe wall surface on the pumping pressure is quantified. Lubrication layer material is sampled and especially produced with similar rheological properties as the former. Pumping pressure is predicted using a combination of the tools of rheology. Abstract: The paper at hand focuses on various methods to characterize the pumpability of fresh concrete. Primarily the rheological behaviours of the concrete as a bulk are described. The study concentrates on the composition and rheological properties of the lubrication layer forming at the interface to the pipeline wall, since this layer is widely considered crucial for concrete pumpability. For this purpose, the material forming the lubrication layer (LL) is sampled from the various concrete mixtures. The results confirm that in addition to the rheological properties of the bulk of fresh concrete, the properties of the lubrication layer and the roughness of the pipe-wall significantly affect concrete flow in pipes. Based on the composition of the concrete and the lubrication layer, it is possible to design the constitutive material of the lubrication layer with properties similar to the one forming in concrete during pumping. It has as well been demonstrated that knowledge of the rheological properties of the lubrication layer is not sufficient to state whether the concrete is pumpable or not. Only a combination of rheological instruments makes the adequate description of concrete pumpability possible.